Pengaruh Sertifikasi dan Motivasi Kerja Terhadap Kinerja Guru SD di UPTD Pendidikan Pemuda dan Olahraga Kecamatan Kauman Kabupaten Tulungagung - Muhamad Rizal Mahtur; Edy Suwasono (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
The problem in this research is the performance of teachers. The purpose of this study was to determine, and analyze the influence of certification and working motivation on the performance of primary schools teachers in UPT Dispendikpora in district Kauman Tulungagung regency either partially or simultaneously. This research is a quantitative approach using associative type, by taking a sample of 44 primary school teachers were in UPT Dispendikpora in district Kauman Tulungagung regency. The results indicate that certification has direct influence on the performance of primary schools teachers in UPT Dispendikpora in district Kauman Tulungagung regency. This means the certification of the program is implement in junior high schools, performance will increase. Working motivation directly influences the performance of primary schools teachers in UPT Dispendikpora in district Kauman Tulungagung regency. Certification and working motivation simultaneously have significant impact on the performance of primary schools techers in UPT Dispendikpora in district Kauman Tulungagung regency. This means the certification of the program is implement properly and teachers have a motivation, the performance of teachers will increase.